Gis-Based Land Suitability Analysis for Ex-Situ Production of Threatened Citropsis articulata in Uganda - Wangalwa, Rapheal; Apio Oleta, Eunice; Kagoro-Rugunda, Grace; Umba Tolo, Casim; Ogwang, Patrick. E.; Barasa, Bernard (Environment & Ecosystem Science (EES), 2021)
Citropsis articulata (Spreng.) is a potent medicinal plant that is increasingly threatened by unsustainable harvesting and habitat destruction due to deforestation. This calls for enhancement of ex-situ conservation of C. articulata through offsite production. However, the success of offsite production of this species heavily rests on precisely assessing the suitability of the land for its production. In this study, an integrated GIS based multi-criteria evaluation approach was used to depict suitable areas for production of C. articulata based on key factors of; climate, soil and topography. Results revealed that only 13.04% (31495.77 km2) of Uganda’s land is very suitable to support natural production of C. articulata and is mainly situated in the western and central regions. Findings further revealed that 76.4% (24062.77 km2) of very suitable land area is situated outside protected areas, thus implying availability of potential sites for ex-situ and commercial production of C. articulata in the country. Findings also indicated that C. articulata has potential of thriving in well drained, moderately acidic soils and pleasantly warm regions endowed with moderately high precipitation and humidity. Since current stocks of C. articulata are mainly restricted to protected areas, cultivating this species will provide alternative sources of the plant harvest. This will help to relieve current pressures on the wild populations of C. articulata, thus providing a safety backup to the current in-situ conservation efforts.
Keywords: Land suitability; Multi-Criteria Evaluation; Citropsis articulata; GIS; Ex-situ production